FKBP10 expression and TP53 mutation predict prognosis and chemotherapy response in triple-negative breast cancer - Yan Li; Chi Zhang; Jian Chen; Gang Tu; Lingfeng Tang (Discover Oncology)
Abstract Background Triple-negative breast cancer (TNBC) lacks targeted therapies. FKBP10 contributes to oncogenesis and chemoresistance. We investigated FKBP10’s prognostic value in TNBC. Methods We retrospectively analyzed 190 TNBC patients receiving neoadjuvant chemotherapy. Patients were stratified by FKBP10 expression (median AOD cutoff) and TP53 status. Cox regression identified prognostic factors for disease-free survival (DFS) and pathological complete response (pCR). Results 34% achieved pCR. High FKBP10 expression correlated with worse DFS (HR = 0.50, 95%CI: 0.26–0.96, P = 0.03). Independent predictors of DFS included: N-stage (P = 0.021), age (P = 0.027), FKBP10/TP53 co-occurrence (P = 0.020), and pCR status (P = 0.005). FKBP10/TP53 co-occurrence predicted poor chemotherapy response (OR = 0.413, P = 0.016). Conclusion FKBP10 overexpression with TP53 mutation predicts poor prognosis and chemoresistance in TNBC. These biomarkers may guide treatment decisions, though prospective validation is needed.